Assessing opportunities to support coral reef climate change refugia in MPAs: A case study at the Revillagigedo Archipelago. (February 2020) - Carter, Amber L.; Wilson, A. Meriwether W.; Bello, Maximiliano; Hoyos-Padilla, E. Mauricio; Inall, Mark E.; Ketchum, James T.; Schurer, Andrew; Tudhope, Alexander W.
Abstract: Coral reef refugia are habitats which possess physical, biological and ecological characteristics that make them likely to be relatively resilient to future climate change. Identification of refugia locations will be important to ensure suitable marine conservation planning is undertaken to protect sites where coral ecosystems will be better preserved now and in the future. This paper presents (1) a review of current knowledge of the oceanographic conditions and coral community in the Revillagigedo Archipelago Large Scale Marine Protected Area, (2) the first assessment of the potential for the Revillagigedo Archipelago to act as a climate refugia site for corals and coral reefs in the eastern tropical Pacific, and (3) consequent management and learning opportunities, to inform reef conservation both locally and globally. Through utilising published literature, remote and in situ environmental data, and field observations it was found that the Revillagigedo area exhibits a combination of distinctive characteristics in the coral community and in oceanographic processes which support conditions of refugia. The potential for refugia is further enhanced due to the absence of significant secondary anthropogenic stressors. This leads to a recommendation to establish the Revillagigedo as a globally significant 'sentinel site' where, through long-term monitoring of oceanographic conditions and of the coral and associated ecosystems, the effects of climate change can be quantified, and the effectiveness of specific refugia attributes established. This information may then be used to underpin the recognition of potential coral refugia elsewhere, and to guide MPA designation and management decisions to enhance their effectiveness. Highlights: Refugia can support the persistence of coral species under climate change conditions. Revillagigedo has environmental conditions with characteristics of refugia. Monitoring at Revillagigedo provides learning opportunity to refine refugia concept. Revillagigedo can serve as a 'sentinel site' to understand climate change impacts.